Analisis nilai diagnostik C-reactive protein pada pasien pediatrik dengan apendisitis di RSUP Dr. Wahidin Sudirohusodo, Makassar, Indonesia - Hermawan Hermawan; Darwati Muhadi; Ibrahim Abdul Samad (DiscoverSys Inc., 2019)
Background : Acute appendicitis associated with acute phase reaction is the most prevalent disease which requires emergency surgery. Its delayed diagnosis and unnecessarily performed appendectomies lead to numerous complications. In our study, we aimed to detect the role of C-reactive protein (CRP) in the exclusion of acute and complicated appendicitis and diagnostic accuracy in pediatric age group.Methods : A retrospective analytic observational study with cross-sectional design was performed on 69 children with definitive appendicitis. Appendectomized patient groups were constructed based on the results of histopathological evaluation. The area under a receiver operating characteristic (ROC) curve (AUC) was performed to examine diagnostic accuracy.Results : Based on cut-off values of ≥ 22,6 mg/dL for CRP level, diagnostic parameters were as follow : sensitivity 97,4%, specificity 80,0%, PPV 97,4%, NPV 80,0%, and diagnostic accuracy 89,9%. AUC values were 0,98 (95% CI 0,96 – 9,99) for CRP.Conclusion : For complicated appendicitis, CRP has the highest degress of diagnostic accuracy. The diagnosis appendicitis should be made primarily based on clinical examination, and obviously more specific and systemic inflammatory markers are needed. Cut-off values of CRP ≥ 22,6 mg/dL provides discrimination values for complicated appendicitis.